Marketing Mix In Influence The Decisions Of Muslim Consumer Using Online Food Delivery Services - Nurotun Jannah; Nasrulloh Nasrulloh (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
This research aims to analyze and show the effect of product, price, promotion, distribution, people, process, and physical evidence on Muslim consumers' decisions to use ShopeeFood services. This study uses a descriptive quantitative approach. Muslim ShopeeFood users in Gresik Regency are the population of this study, where the number is unknown. The sampling technique used random sampling by measuring the number of samples using the unknown population approach to obtain a total sample of 100 respondents. The research uses primary data in the form of questionnaires and secondary data in the form of literature. Data were analyzed using multiple linear regression, but first tested the validity, reliability, and classical assumptions. The results of this study indicate that product, price, promotion, distribution, process, and physical evidence positively and significantly influence Muslim consumers' decisions to use ShopeeFood services. Meanwhile, the person variable does not influence the Muslim consumer's decision to use ShopeeFood services. The decision of Muslim consumers to use ShoeeFood's services is significantly influenced by product, price, promotion, distribution, people, process, and physical evidence factors. This research can be used as a reference for online food delivery service providers, especially ShopeeFood, in marketing management to increase sales transactions, especially in Gresik Regency.